2004
DOI: 10.1007/978-3-540-30217-9_101
|View full text |Cite
|
Sign up to set email alerts
|

Evolving the “Feeling” of Time Through Sensory-Motor Coordination: A Robot Based Model

Abstract: Abstract. In this paper, we aim to design decision-making mechanisms for an autonomous robot equipped with simple sensors, which integrates over time its perceptual experience in order to initiate a simple signalling response. Contrary to other similar studies, in this work the decisionmaking is uniquely controlled by the time-dependent structures of the agent's controller, which in turn are tightly linked to the mechanisms for sensory-motor coordination. The results of this work show that a single dynamic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Nolfi (2002) and Croon et al (2004) investigate a task in which a robot is evolved to recognise whether it is located in one room rather than another, when navigating a maze. Tuci et al (2004Tuci et al ( ,2005 report an intriguing investigation in which the evolved control system of a simulated Khepera robot is shown to be able to change its behaviour as a result of its experience of the environment. More specifically, the robot is able to discriminate between the equivalents of productive and unproductive foraging situations.…”
Section: Separating the Various Swarm Areasmentioning
confidence: 99%
“…Nolfi (2002) and Croon et al (2004) investigate a task in which a robot is evolved to recognise whether it is located in one room rather than another, when navigating a maze. Tuci et al (2004Tuci et al ( ,2005 report an intriguing investigation in which the evolved control system of a simulated Khepera robot is shown to be able to change its behaviour as a result of its experience of the environment. More specifically, the robot is able to discriminate between the equivalents of productive and unproductive foraging situations.…”
Section: Separating the Various Swarm Areasmentioning
confidence: 99%
“…On the explicit modelling side, a most simple approach is to retain all sensory information in the last T time steps, as done in classifier systems [3]; a more elaborate and demanding approach proceeds by encoding every possible situation of the robot in the search space [4]. Implicit memory modelling mostly proceeds by representing robotic controllers as recurrent neural nets (NN) [5], [6], [7], allegedly coding the memory of the previous time steps within the neuron states.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that some "reactive" robots employ internal state to deal with perceptual aliasing and their control systems are not actually purely reactive [3]. Recently some researchers studied recurrent neural networks and plastic mechanism to solve real-world robotic problems [21,8,5]. It has been shown that the dynamic property in the neural networks can handle perceptually aliased problems without difficulty.…”
Section: Introductionmentioning
confidence: 99%